The Design of Procurement Contracts - Rob, Rafael (American Economic Review, 1986)
This paper investigates the interaction between bidding for procurementprograms and fractional buys. This problem is analyzed from the standpoint of a cost-minimizing procuring agent. It is shown that underimperfect competition, a multiple-source purchase is generally preferred to a single-source contract. Similarly, the author demonstrates that a (strictly) intermediate cost sharing arrangement, i.e., an incentive contract, dominates either the cost-plus or the firm-fixed price arrangements. Copyright 1986 by American Economic Association.